2020
DOI: 10.1200/go.20.00326
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Perceptions of Surgical Cancer Care in the Era of COVID-19: A Global Cross-Sectional Study

Abstract: PURPOSE The rapid dissemination of information through social media renders a profound lens to evaluate perceptions of emerging topics, especially in the context of a global pandemic. The primary objective of this cross-sectional study was to elucidate trends on social media in the setting of surgical cancer care affected by the COVID-19 pandemic across the globe. METHODS A public search of Twitter from April 1 to 30, 2020, was conducted, which yielded 996 posts related to COVID-19 and cancer. Two authors (E.J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A survey of 343 oncologists from 28 countries on the impact of COVID-19 on decision-making showed that the majority stated that they would use less chemotherapy, immune checkpoint inhibitors and/or steroids, and would be more hesitant to use second-or third-line therapies for patients with advanced cancer [52,57]. Cancellations of cancerrelated surgeries were around 40.1%, especially in breast, lung, and urological cancer [58]. Treatment modification has been observed in all lines of therapy: 41.4% in perioperative care, 62.9% in palliative, and 76% in endocrine treatments [59].…”
Section: Covid-19 and Its Impact On Cancer Care Deliverymentioning
confidence: 99%
“…A survey of 343 oncologists from 28 countries on the impact of COVID-19 on decision-making showed that the majority stated that they would use less chemotherapy, immune checkpoint inhibitors and/or steroids, and would be more hesitant to use second-or third-line therapies for patients with advanced cancer [52,57]. Cancellations of cancerrelated surgeries were around 40.1%, especially in breast, lung, and urological cancer [58]. Treatment modification has been observed in all lines of therapy: 41.4% in perioperative care, 62.9% in palliative, and 76% in endocrine treatments [59].…”
Section: Covid-19 and Its Impact On Cancer Care Deliverymentioning
confidence: 99%
“… 13 The treatment modification was observed across all lines of therapy, ie, adjuvant and neoadjuvant (41.4%), palliative (62.9%), or injectable endocrine or bone-modulating only (76.0%) treatments. For cancer-related surgery, Keil et al 14 reported results of a Twitter survey that provided insight into the impact of COVID-19 on the global discussion surrounding surgical cancer care. An essential topic for debate analyzed via Twitter posts was the cancellation of cancer-related surgeries (40.1%), of which the most common types mentioned were breast cancer, lung cancer, and urologic cancer.…”
Section: Covid-19 and Impact On Cancer Care Deliverymentioning
confidence: 99%